Implementasi Aktivitas Motorik kasar Anak Usia Dini Melalui Kegiatan Bermain Outdoor di TK Plus An Naafi - Ulfah, Fitria; Khoiriah, Fadila Aisyatul (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
Along with advances in technology, there is a phenomenon of using gadgets among children which is attracting quite a lot of attention. This is because the exixtence of sophisticated technology has brought changes to children’s daily lives, we can see that children spend more time playing on cellphones. So too much dependence on technology can also have negative impact. These include making children tend to spend time in front of electronic device screens, which results in the child’s gross motor skills not being properly stimulated because the child’s physical activity desreases. This research was conducted at Kindergarten Plus An Naafi using a qualitative approach with the case study method. The data collection process is through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this research are the implementation of gross motor activities for early childhood at Plus An Naafi Kindergarten which has a significant positive impact on children’s physical and motor development. Through outdoor activities children can improve muscle coordination and balance skills. In addition, this research provides an overview of the obstacles faced in implementing gross motor activities.  Keyword: Gross Motor Skills; Early Childhood; Outdoor Play